Konsep Hukum Administrasi Lingkungan Dalam Mewujudkan Pembangunan Berkelanjutan - Mukhlish Mukhlish (The Constitutional Court of the Republic of Indonesia, 2010)
Nowadays, Enviromental issue is not belong to Individual or bilateral issue merely, it has becornara collective responsibility of all people in the world. We can say that any pollution and environmental damage almost reach out the highest culmination. A conjungture enviromental disaster almost occurred in all over epicentrum of the world, including Indonesia. It will be an undebatable proof that between human and nature in the context of enviromental management is getting to be unfriendly. Thus, prevailing every existing issue, needs a progressive and integrative legal breakthrough, which is become one of elegant solution for sake of suistainable development purposes. Therefore, hopefully, the estuary of this writing is attempt to give alternative idea to development of the concept of legal administrative oversight, which will be a reference for development of administrative law and currently as a correction of the oversight of enviromental administration all at once.